The Factors That Influence Employee Retention and its Impact on Organizational Citizenship Behavior and Job Embeddedness: A Study at the Public Sector Organizations in Malaysia - Asiah Ali (Universiti Sains Islam Malaysia, 2024)
Research related to employees’ retention is very significant, particularly in the context of public sector organization in Malaysia. It is due to the level of employee retention in this context is considered high. Therefore, this study is conducted to address three issues related to employee retention in this context. First, to examine the factors that influence employee retention. Specifically, this study examine the effect of human resource management practice, organizational learning culture, transformational leadership and peer support on employee retention. Second, to examine the impact of employee retention on organizational citizenship behaviour and job embeddedness. Third, to investigate the role of employee retention as a mediator in the relationship between human resource management practice, organizational learning culture, transformational leadership and peer support, organizational citizenship behaviour and job embeddedness. The data of this study have been collected through survey among 1110 supporting staff employees of public sector organization that based in Putrajaya, Malaysia. The data have been analysed with structural equation model technique. This study has found three factors that influence employee retention in the context public sector organizations in Malaysia. The factors are human resource management practice, organizational learning culture and peer support. In addition, this study provides empirical evidence about the role of employee retention as a mediator between retention factors (human resource management practice, organizational learning culture and peer support) and organizational citizenship behaviour and job embeddedness.